The influence of female CEOs on bank performance in Indonesia - Sabila, Fahira Sal; Dalimunthe, Sholatia; Shadiq, Naufal (Global Advances in Business Studies, 2023)
The purpose of this study is to determine the influence of female Chief Executive Officers (CEOs) on the performance of banking companies listed on the Indonesia Stock Exchange for the period 2010-2018. The independent variable used in this study was female. The dependent variables used in this study are company performance which is proxied with Return on Assets (ROA) and Capital Adequacy Ratio (CAR). The source of data used in this study is in the form of financial statements of banking companies listed on the Indonesia Stock Exchange for the period 2010-2018. The sampling method used in this study used purposive sampling techniques. The model used in this study is panel data with a Fixed Effect Model approach. The results obtained from this study that CEO gender has a significant effect on ROA and CAR n